A Turbulent Adolescence Ahead: The ICC’s Insistence on Disclosure in the Lubanga Trial - Christodoulos Kaoutzanis (Washington University Global Studies Law Review, 2013)
The completion of the first trial at the International Criminal Court (ICC) against Thomas Lubanga Dyilo was a great milestone for international criminal justice. Despite this obvious accomplishment, this article argues that the Trial Chamber’s solutions to two evidentiary problems will restrict the ICC’s potential to effectively hear future cases. First, this article presents the details behind the two evidentiary problems of disclosure: that of exculpatory confidential information and that of the identities of the prosecutor’s intermediaries. This analysis is exhaustive in order to highlight the challenges that the Prosecutor faced and the manner in which the ICC Chambers responded. The article then demonstrates how the Chamber’s focus on the fairness of the Lubanga trial has undermined the ICC’s greater goal of ending impunity and achieving accountability for international criminal acts. This article seeks to highlight two areas of concern for the ICC’s future as an international court which, if left unaddressed, may harm international justice disproportionately more than the benefits conferred upon it by the Lubanga case.
Keywords: ICC; Lubanga; international criminal justice; Trial Chamber; Prosecutor; impunity; evidence; disclosure